Determining the in-plane orientation of the ground-state orbital of CeCu2Si2 - Willers, Thomas; Haverkort, Maurits W. (Arxiv, 2012)
We have successfully determined the hitherto unknown sign of the B44 Stevens crystal-field parameter of the tetragonal heavy-fermion compound CeCu2Si2 using vector q dependent non-resonant inelastic x-ray scattering (NIXS) experiments at the cerium N4,5 edge. The observed difference between the two different directions q||[100] and q||[110] is due to the anisotropy of the crystal-field ground state in the (001) plane and is observable only because of the utilization of higher than dipole transitions possible in NIXS. This approach allows us to go beyond the specific limitations of dc magnetic susceptibility, inelastic neutron scattering, and soft x-ray spectroscopy, and provides us with a reliable information about the orbital state of the 4f electrons relevant for the quantitative modeling of the quasi-particles and their interactions in heavy-fermion systems.
Die Ziffer 2 im Titel ist zweimal tiefgestellt
Gesehen am 27.11.2017